Daylight and plant growth in woodland: What are the main factors for the woodland manager to consider?. Issue 2 (3rd April 2017) - Helliwell, Rodney
Abstract: In cloudy regions such as Great Britain, diffuse light from the sky is the only source of light for a large part of the time. Additionally, within woodland, trees are also likely to obscure direct sunlight for most of the time, even when there is no cloud cover. I had, therefore, assumed that direct sunlight would be of lesser significance than diffuse light for the growth of tree seedlings and other vegetation within woodland. The literature on this subject appears to be somewhat confusing and contradictory; and any guidelines, which are provided by one author, are likely to be in conflict with the conclusions of at least some other authors. The aims of this research were therefore to carry out a very small experiment in an attempt to clarify these conflicting views. The results of this experiment were not what I would have predicted, and further work (by myself or others) appears to be needed in order to clarify the factors which are of greatest relevance to the woodland manager.